KEBIJAKAN UJI EMISI GAS BUANG KENDARAAN BERMOTOR DI KOTA DUMAI : STUDI KASUS UJI EMISI KENDARAAN BERMOTOR RODA DUA DAN RODA EMPAT TAHUN 2015-2016 - Akbar, Syah Reza; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the issuance of Dumai Mayor Relegation No 15 of 2014 about Motor Car Testing and Motorized Emission Test of Motor Vehicle Disposal. Since the regulation was issued, in the implementation of the emission test policy regulated in the Mayor Regulation Dumai No. 15 of 2014 is still encountered various problems, especially on two-wheeled and four-wheeled vehicles. As the result of the information gained, public awareness of Dumai City on the implementation and emission test obligations on the two-wheels and four wheels is still low and there are still many motor vehicles that have not followed the emission test resulting in not achieving the established retribution targets. The purpose of this study is to determine the content of policies and inhibiting factors in the implementation of emission test policy on two-wheeled and four-wheeled vehicles in Dumai City in 2015 - 2016. The method used in this research is descriptive research with qualitative approach method. The type of research data is primary data and secondary data. Data collection techniques in this study are interviews and documentation. Technical analysis of data used is descriptive qualitative data analysis. The results showed that the implementation of the emission test policy on twowheeled and four-wheeled vehicles has not been run in accordance with the contents of the regulations that should be the guidance of policy implementation by UPT. PKB and Dinas Perhubungan of Dumai City. The inhibiting factors in the implementation of emissions test on two-wheeled and four-wheeled vehicles are not yet firmly implemented policies, socialization has not been done optimally, weak of supervision by the Dumai City Council and there has been no public or private garage shop that became the implementer, so that in the implementation process becomes ineffective and inefficient. The right solution to overcome these problems is to improve the socialization effectively and improve coordination and communication between relevant implementing agencies, so that its implementation in accordance with what has been stated in the Dumai Mayor Relegation No 15 of 2014. Keywords: Policy, Emission Test.